2002
DOI: 10.1021/ac0156619
|View full text |Cite
|
Sign up to set email alerts
|

High-Density Fiber-Optic Genosensor Microsphere Array Capable of Zeptomole Detection Limits

Abstract: The detection limit of a fiber-optic microsensor array was investigated for simultaneous detection of multiple DNA sequences. A random array composed of oligonucleotide-functionalized 3.1-microm-diameter microspheres on the distal face of a 500-microm etched imaging fiber was monitored for binding to fluorescently labeled complementary DNA sequences. Inherent sensor redundancy in the microarray allows the use of multiple microspheres to increase the signal-to-noise ratio, further enhancing the detection capabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
107
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(110 citation statements)
references
References 19 publications
3
107
0
Order By: Relevance
“…Optical fiber microwell/microbead arrays have been applied to nucleic acid biosensing [88]. The microspheres were encoded with a fluorescent dye, functionalized with probe oligonucleotides and immobilized in microwells of etched imaging fiber.…”
Section: Sensing Schemesmentioning
confidence: 99%
“…Optical fiber microwell/microbead arrays have been applied to nucleic acid biosensing [88]. The microspheres were encoded with a fluorescent dye, functionalized with probe oligonucleotides and immobilized in microwells of etched imaging fiber.…”
Section: Sensing Schemesmentioning
confidence: 99%
“…Although some preliminary data suggested that the platform is capable of high sensitivity (Epstein et al 2002), a number of significant challenges had to be overcome in order to create a robust, quantitative, high-performance system suitable for use with biological samples such as mammalian poly(A + ) mRNA. We have now developed such a system.…”
mentioning
confidence: 99%
“…Chemical etching is a commonly used technique in optical fabrication, such as nanoprobes [51], and microwells [52] . The general idea is to use hydrofluoric acid (HF) to etch the fiber tip.…”
Section: Fabricationmentioning
confidence: 99%